Analysis of the Implementation of K3 Promotion at Pt Indokomas Buana Perkasa (Gitet PLN 500 Kv Perawang Development Project, Tualang) in 2022: Analisis Penerapan Promosi K3 Di PT Indokomas Buana Perkasa (Proyek Pembangunan Gitet PLN 500 Kv Perawang, Tualang) Tahun 2022 - Putri Delima Romania Silaban; Hetty Ismainar; Muhamadiah Muhamadiah; Firman Edigan; Yuyun Priwahyuni (Badnur Medisa Group, 2022)
The implementation of occupational safety and health promotion is an activity in the workplace designed to help workers and companies in terms of improving and improving health with the direct participation of workers and management. Workers have not been able to implement the implementation of K3 promotion because there is still a lack of awareness of workers how important it is to maintain safety at work. The purpose of this study is to determine the application of K3 promotion at PT Indokomas Buana Perkasa (GITET PLN 500 KV Perawang, Tualang development project) in 2022. This research uses qualitative methods. The informants in this study totaled 5 people consisting of site managers, K3 staff and 3 workers, qualitative data were carried out with interviews and observations using cheeklist sheets. The results of this study can be concluded that the implementation of K3 promotion at PT Indokomas of the GITET PLN 500 KV development project is quite good, the K3 signs and K3 policies are good, the K3 policy and K3 training need to be updated and carried out again. It is hoped that the company will pay more attention to every aspect of K3 promotion in order to maintain the safety of workers.